2012
DOI: 10.1055/s-0032-1312876
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Reader Agreement of Multi-Parametric MR Imaging for the Detection of Prostate Cancer: Evaluation of a Scoring System

Abstract: The use of a simple 5-point scoring system for T2-weighted images, DWI, and DCE-MRI is feasible in functional prostate MRI and has high inter-observer reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our study also confirmed previous results by Schimmöller et al 25 and Quentin et al, 26 who have shown that the PI-RADS scoring system has good to moderate interrater agreement.…”
Section: Resultssupporting
confidence: 92%
“…Our study also confirmed previous results by Schimmöller et al 25 and Quentin et al, 26 who have shown that the PI-RADS scoring system has good to moderate interrater agreement.…”
Section: Resultssupporting
confidence: 92%
“…Turbo spin echo sequences were used to acquire T2-weighted images in standard orthogonal planes: axial (TR, 10 3). For axial diffusion-weighted imaging (DWI), a single-shot spin-echo echo-planar sequence was used (TR, 4,600 ms; TE, 90 ms; FOV, 20.4 cm; voxel size, 1.5 Â 1.5 Â 3.0 mm; image matrix, 136 Â 136; using GRAPPA parallel imaging scheme with acceleration factor 2; scan time, 7:12 min).…”
Section: Mr Techniquesmentioning
confidence: 99%
“…The mean score of all lesions for T2-weighted images was 3.56 AE 0.86 (range, [1][2][3][4][5]. For DWI the mean score was 3.10 AE 1.38 (range, 1-5), and for DCE-MRI the mean score was 3.34 AE 1.29 (range, 1-5).…”
Section: Scoring: Different Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found good interobserver agreement for the detection of high-grade prostate cancers by MRI, suggesting that our results are reproducible in this clinical setting. The implementation of multiparametric MRI and structured, standardized reporting could further increase interobserver agreement [22]. It must be noted, however, that all three readers were experienced in interpreting conventional endorectal prostate MRI, and experience has been found to be crucial for the diagnostic accuracy of prostate MRI [23].…”
Section: Figmentioning
confidence: 99%